Internet Addiction in Youngsters and its Relationship with Anxiety, Depression, Stress, and Self-esteem (International Journal of Food and Nutritional Sciences, 2021)
In today's burgeoning modern times of digitalizing, there is more access than ever to digitaldevices. To make our lives easier and quicker, digital technology is constantly evolving and theinternet has become an integral part of our life. Paralleling the rapid increase in internet smash,there is a rise in internet addiction especially among young adults.